2004
DOI: 10.7861/clinmedicine.4-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Medical outpatients: changes that can benefit patients

Abstract: -This article reviews the current literature relating to medical outpatient services. It has been produced as part of the RCP/NHS Confederation working party on outpatients departments. The article deals with surveys of patient views on outpatients, suggested ways of improving the service, and how best to accommodate teaching in this setting. An RCP booklet, 'How user friendly is your outpatient department?', has also been produced and is available from the college. KEY WORDS: ambulatory care, appointment, boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
0
38
1
Order By: Relevance
“…The role of the interactive factors in determining quality in the outpatient journey was also noted in a meta-analysis by Saila et al [30] that identified the importance of the consultation with the doctor, effective communication and the establishment of a trustful yet professional patientdoctor relationship. Our findings contrast with the results of studies that have placed an emphasis on process aspects of the outpatient journey including waiting times for a first appointment and in the waiting room [25] and time in consultation [35]. By comparison, published studies in oncology patients suggest that waiting times, environmental factors and aspects of patient-doctor interaction [36] may all be relevant to a satisfactory experience.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The role of the interactive factors in determining quality in the outpatient journey was also noted in a meta-analysis by Saila et al [30] that identified the importance of the consultation with the doctor, effective communication and the establishment of a trustful yet professional patientdoctor relationship. Our findings contrast with the results of studies that have placed an emphasis on process aspects of the outpatient journey including waiting times for a first appointment and in the waiting room [25] and time in consultation [35]. By comparison, published studies in oncology patients suggest that waiting times, environmental factors and aspects of patient-doctor interaction [36] may all be relevant to a satisfactory experience.…”
Section: Discussioncontrasting
confidence: 85%
“…This included four domains from a qualitative assessment of patients' attitudes of the gastroenterology outpatient experience by two trained junior doctors using open questions, three domains from the national outpatient survey and a report of the key domains associated with satisfaction from the national outpatient survey [12] and three domains from a published, validated endoscopy-related patient evaluation [19,20]. These domains and a review of studies from the published literature [24][25][26][27] were used to identify aspects of the outpatient pathway that related to experiential quality. A composite, quantitative, self-completed patient questionnaire (Appendix 1) was then designed in two parts.…”
Section: Survey Design and Developmentmentioning
confidence: 99%
“…Often they were seen by a registrar rather than the consultant, which is common practise within the British NHS. 24 However, the registrar was referred to as the ''understudy'' by one participant (Sophie), which underlines the women's feeling that they were not seen as important. Several of the participants noted that no-one seemed to be joining the dots and integrating their health care:…”
Section: Resultsmentioning
confidence: 99%
“…management of waiting times is considered to be among the most important factors contributing to patient satisfaction [6,7]. A 1-h delay in the scheduled start time is associated with patients' complaints [8].…”
Section: Key Pointsmentioning
confidence: 99%